Pengembangan Tes Penguasaan Konsep Two Tier Multiple Choice pada Materi Kalor Menggunakan Model Rasch - Ananda Putri, Novia; Winny Liliawati; Ridwan Efendi (Jurnal Pendidikan dan Ilmu Fisika, 2024)
One of the objectives of high school physics lessons is to ensure that students master the concepts being taught. For that reason, a test instrument is needed that can accurately measure concept mastery. In this regard, teachers need innovation in the form of developing two-tier multiple choice test instruments. This study aims to evaluate the feasibility of the test instrument on the topic of heat. The method used in this research is research and development (R&D), adapting the instrument development steps using the Rasch model. The developed test instrument consists of 12 items, divided into three categories: 3 items with high difficulty level, 8 items with medium difficulty level, and 1 item with easy difficulty level. Based on the analysis using ministep software version 5.6.4.0, it was found that this test instrument is valid and reliable, with a Cronbach alpha value of 0.71, which falls into the good category, and is able to differentiate students' concept mastery based on high, medium, and low ability levels. This analysis shows that the developed test instrument can be used to measure students' concept mastery ability.